PENGOLAHAN BROWNIES KUKUS KETAN HITAM DI HOTEL SAVOY HOMANN BIDAKARA BANDUNG - Rini Rahma Dini; Oda Oda; Rian Andriani (Jurnal Pariwisata, 2014)
Abstract - World tourism is closely related to the hotel or pastry and bakery offers a wide range of products, including cakes, pies, cookies, ice cream candy / nougat. Savoy Homann Bidakara Hotel Bandung providing pastry products, namely black sticky rice steamed brownies. This product consists of Black Sticky Rice flour mixed with dark chocolate and blueberry jam and presented in a box as for the use cupcase mica. Shaped like a cupcake and garnished with sliced fruits such as strawberry, cherry green and Sunkist and very attractive so tempting guests to enjoy.In making Black Sticky Rice steamed brownie must same as standard recipe for the result product was stabil, this product is very unique and interesting as the black sticky rice garnish brownies are served with a slice of fruit. This product is in Savoy Homann Hotel Bidakara Bandung. But the product Black Sticky Rice Steamed Brownies has a disadvantage that consumer interests who prefer brownies the other products compared with Black Sticky Rice steamed brownies. This it should Black Sticky Rice Steamed Brownies is beautiful in it’s presentation garnished more and more tidy so that more guests are interested in this product. Keyword : Brownies Kukus Ketan Hitam, Food Processing.  Abstrak - Dunia pariwisata erat kaitannya dengan hotel atau pastry and bakery menyediakan berbagai macam produk, diantaranya cake, pie, cookies, ice cream permen / nougat. Savoy Homann Bidakara Hotel Bandung menyediakan produk pastry yaitu brownies kukus ketan hitam. Produk ini terdiri dari tepung ketan hitam yang dipadukan dengan dark chocolate serta blueberry jam dan disajikan dalam sebuah box mika adapun yang menggunakan cupcase. Yang dibentuk seperti cupcake dan di-garnish dengan irisan buah-buahan seperti strawberry, green cherry dan sunkist dan di tata dengan sangat menarik sehingga menggugah selera tamu untuk menikmatinya. Produk ini sangat unik dan menarik karena garnish brownies kukus ketan hitam tersebut disajikan dengan beberapa slice fruit. Produk ini ada di Savoy Homann Bidakara Hotel Bandung. Dalam Pembuatan Brownies Kukus Ketan Hitam ini harus sesuai dengan standard recipe agar produk yang dihasilkan selalu stabil, namun produk Brownies Kukus Ketan Hitam ini mempunyai kekurangan yaitu minat konsumen yang lebih memilih produk brownies yang lain dibandingkan dengan brownies kukus ketan hitam. Maka dari itu sebaiknya Brownies Kukus Ketan Hitam ini dalam penyajiannya digarnish lebih indah dan lebih rapih agar tamu lebih tertarik dengan produk ini. Kata Kunci : Brownies Kukus Ketan Hitam, Pengolahan Makanan